Applied Mathematics in Genetic Resources: Toward a Synergistic Approach Combining Innovations with Theoretical Aspects - Bari, Abdallah; Chaubey, Yogendra; Sillanpää, Mikko J.; Stoddard, Fred; Damania, Ardeshir B.; Alaoui, Si Bennasseur; Mackay, Michael (CRC Press, 2016)
A chapter highlighting the importance of gene flow in the book "Applied Mathematics and Omics to Assess Crop Genetic Resources for Climate Change Adaptive Traits".